The Concept of Islamic Education Curriculum Based on Muhaimin’s Perspective and Its Relevance in the Context of Contemporary Islamic Education - Amali, Muhlas; Siswanto, Siswanto; Solichin, Mohammad Muchlis (Afkaruna: International Journal of Islamic Studies (AIJIS), 2025)
In today’s dynamic era, Islamic education (PAI) in Indonesia faces serious challenges such as increasing corruption, violence, and deviant behavior among students. Society needs educational solutions that not only educate academically but also form strong religious and moral characters so that relationships between people can be more harmonious. In this context, the concept of education that is integrative and responsive to Islamic values ​​is very important to build a young generation with noble character. This study aims to explore and analyze the concept of the PAI curriculum based on Muhaimin’s perspective and its relevance in contemporary education. Using a descriptive qualitative approach, this study analyzes various literature sources to gain in-depth insights. The results of the study indicate that PAI education must adapt to modern learning methods such as problem-based learning and contextual teaching and learning to encourage the development of students’ soft skills. This study makes a significant contribution to the development of a relevant PAI curriculum and answers the challenges of Islamic education in Indonesia.